Clinical outcomes of treatment of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis based on ANCA type. Issue 6 (30th November 2015) - Unizony, Sebastian; Villarreal, Miguel; Miloslavsky, Eli M; Lu, Na; Merkel, Peter A; Spiera, Robert; Seo, Philip; Langford, Carol A; Hoffman, Gary S; Kallenberg, CG M; St. Clair, E William; Ikle, David; et al.
Abstract : Objective: To evaluate whether the classification of patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) according to ANCA type (anti-proteinase 3 (PR3) or anti-myeloperoxidase (MPO) antibodies) predicts treatment response. Methods: Treatment responses were assessed among patients enrolled in the Rituximab in ANCA-associated Vasculitis trial according to both AAV diagnosis (granulomatosis with polyangiitis (GPA)/microscopic polyangiitis (MPA)) and ANCA type (PR3-AAV/MPO-AAV). Complete remission (CR) was defined as disease activity score of 0 and successful completion of the prednisone taper. Results: PR3-AAV patients treated with rituximab (RTX) achieved CR at 6 months more frequently than did those randomised to cyclophosphamide (CYC)/azathioprine (AZA) (65% vs 48%; p=0.04). The OR for CR at 6 months among PR3-AAV patients treated with RTX as opposed to CYC/AZA was 2.11 (95% CI 1.04 to 4.30) in analyses adjusted for age, sex and new-onset versus relapsing disease at baseline. PR3-AAV patients with relapsing disease achieved CR more often following RTX treatment at 6 months (OR 3.57; 95% CI 1.43 to 8.93), 12 months (OR 4.32; 95% CI 1.53 to 12.15) and 18 months (OR 3.06; 95% CI 1.05 to 8.97). No association between treatment and CR was observed in the MPO-AAV patient subset or in groups divided according to AAV diagnosis. Conclusions: Patients with PR3-AAV respond better to RTX than to CYC/AZA. An ANCA type-based classification may guide immunosuppression in AAV. Trial registration number: NCT00104299; post-results.